Design and Development of a Sealing Machine for Black Mulberry Product Packaging at Renkofruit Fam SME, Ciwidey - Ni Ketut Mega Diana Putri; Dino Caesaron; Iphov Kumala Sriwana; Ilma Mufidah (Jurnal Pengabdian Masyarakat dan aplikasi Teknologi, 2026)
Mulberry (Morus nigra) is one of the plants widely utilized by small and medium enterprises (SMEs), including RENKOFRUIT FAM SME located in Ciwidey, Indonesia. The utilization of mulberry has been chosen due to its high economic value through the diversification of downstream products. However, in the process of product diversification, packaging adhesion issues have emerged, potentially compromising product quality during distribution. The objective of this community service program is to design and develop a sealing machine to address these packaging challenges and improve product quality. The design process applies the VDI (Verein Deutscher Ingenieure) methodology, which consists of four systematic stages: clarification of the task, conceptual design, embodiment design, and detail design. This structured design approach allows for a more thorough and optimal product development process. The outcomes of this community engagement activity is the application of designed sealing machine at Renkofruit Fam SME, Ciwidey. From a managerial perspective, the sealing machine is expected to enhance packaging quality, extend distribution coverage across the country, and contribute to increased profitability for the targeted SME. This study demonstrates the application of systematic engineering design to support local SMEs in improving product competitiveness and sustainability.